Virtual Reality As A Tool In The Education - GUPT, ASHOO (NeuroQuantology, 2023)
The usage of VR is on the rise in the classroom because it gives students greater freedom to learn by doing. In this work, we provide an educational programme for use in either face-to-face or online classes on the topic of formal languages; it allows students to virtually investigate, analyse, and learn more about a given topic. This paper introduces an educational software that uses 3D object manipulation to make learning about automata, regular expressions, and automaton minimization much simpler for students. The software has a straightforward interface and is straightforward to use. The software incorporates the programming language PHP (Hypertext Pre-Processor) for web page publication and the 3D modelling tools Blender and VRML (Virtual Reality Modelling Language) for automaton creation. The results achieved using the created software demonstrate the characteristics that make the perfect Virtual Reality for scenarios of study and learning, transferring the discipline as a point of reference from the educational setting to the computer laboratories and making the subject matter more engaging for the student and the learning process simpler